PEMETAAN DAERAH PENANGKAPAN IKAN CAKALANG (Katsuwonus pelamis) DI WILAYAH PENGELOLAAN PERIKANAN 572 YANG DIDARATKAN PELABUHAN PERIKANAN SAMUDERA NIZAM ZACHMAN JAKARTA - Sania Pareka Sania Pareka; Gilang Rusrita Aida; Achmad Kusyairi; Sartono Marpaung; Kuncoro Teguh Setiawan (Jurnal Perikanan Unram, 2024)
The Fisheries Management Area of the Republic of Indonesia 572 (WPP-RI 572) is a marine area covering the waters of the Indian Ocean west of Sumatra and the Sunda Strait, which has the potential for dominant marine resources, particularly the capture of skipjack tuna (Katsuwonus pelamis). Determining fishing areas can be estimated based on the conditions of the marine region. The habitat of a species is usually described by oceanographic parameters. Sea Surface Temperature (SST) and Chlorophyll-a are important oceanographic parameters to determine the presence of skipjack tuna and facilitate the analysis of fishing areas. Therefore, this research aims to map the skipjack tuna fishing areas in WPP-RI 572, which is landed at the Nizam Zachman Ocean Fishery Port in Jakarta, based on the distribution of sea surface temperature and chlorophyll-a in WPP-RI 572. The method used in this research is a quantitative descriptive method, and the data used are secondary data in the form of SST satellite image data, chlorophyll-a obtained from NASA Ocean Color and Earth data, and other supporting data, as well as the collection of coordinate point data taken from logbook data and skipjack tuna catch data obtained from the Nizam Fishing Base, Jakarta. The data is then analyzed statistically using multiple linear regression analysis. The research results show that oceanographic parameters such as sea surface temperature and chlorophyll-a significantly influence the amount of skipjack tuna catches in WPP-RI 572.